2017
DOI: 10.1111/and.12903
|View full text |Cite
|
Sign up to set email alerts
|

Association between promoter methylation of MLH1 and MSH2 and reactive oxygen species in oligozoospermic men-A pilot study

Abstract: MLH1 and MSH2 are important genes for DNA mismatch repair and crossing over during meiosis and are implicated in male infertility. Therefore, the methylation patterns of the DNA mismatch repair genes MLH1 and MSH2 in oligozoospermic males were investigated. Ten oligozoospermic patients and 29 normozoospermic donors were analysed. Methylation profiles of the MLH1 and MSH2 promotors were analysed. In addition, sperm motility and seminal reactive oxygen species (ROS) were recorded. Receiver operating characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 27 publications
0
28
1
Order By: Relevance
“…Infertility affects about 15% of couples and 12% of men during their reproductive years, and male infertility is responsible for half of these infertility cases (Agarwal et al, ; Gunes, Arslan, Hekim, & Asci, ). The aetiology is unknown in about 30% of male infertility cases (Gunes et al, ). Genetic factors are highlighted as the most frequent male infertility causes.…”
Section: Introductionmentioning
confidence: 99%
“…Infertility affects about 15% of couples and 12% of men during their reproductive years, and male infertility is responsible for half of these infertility cases (Agarwal et al, ; Gunes, Arslan, Hekim, & Asci, ). The aetiology is unknown in about 30% of male infertility cases (Gunes et al, ). Genetic factors are highlighted as the most frequent male infertility causes.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the p53‐related genes in our results were previously studied in humans or animals. In humans, the level of MLH1 methylation in NOA patients is significantly higher than that in healthy subjects and is positively correlated with the level of reactive oxygen species (ROS; Gunes et al, ). Moreover, a recent human study indicated that single nucleotide polymorphisms (SNPs) of PARP1 are highly associated with oligospermia (Chen, Pu, Zhang, & A, ).…”
Section: Discussionmentioning
confidence: 99%
“…For somatic cell lysis, first an aliquot of liquefied ejaculate sample containing <10 × 10 6 /ml spermatozoa was added into a test tube and centrifuged for 8 min at 1,500 × g to remove the seminal plasma. After washing this pellet with 1 ml of 1× PBS, the pellet was treated with 12 ml of somatic cell lysis buffer (0.5% Triton X‐100 and 0.1% sodium dodecyl sulphate [SDS] in 200 ml of distilled water) on ice for 30 min (Gunes et al, ). Subsequently, the supernatant was removed by centrifugation for 15 min at 300 × g .…”
Section: Methodsmentioning
confidence: 99%
“…After the complete elimination of somatic cells, the sperm DNA was isolated with QIAamp DNA Mini kit (Qiagen) according to the manufacturer's instructions (Gunes et al, ). DNA samples were stored at −80ºC until bisulphite modification step.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation